Hybrid Carbohydrate–Lipid Nanocarriers: In Vitro Efficacy Gene-Rated by Association of UV-Absorbers and Raspberry Polyphenols Rich-Fraction - Nicoleta Badea; Diego Samayoa; Alina Moroşan; Cristina Ott; Ioana Lacatusu (Pharmaceuticals)
Background/Objectives: The study aims to investigate an improved version of lipid nanocarriers (NLCs) (formulated with functional coconut butter and marula oil) by designing hyaluronic acid (HA) decorated NLC co-loaded with dual UVA (butyl methoxy dibenzoyl methane, BMDBM), UVB absorbers (ethyl-hexyl-salicylate, EHS) and a Raspberry rich polyphenols fraction (RPRF) for development of more natural NLC-based to-pical formulations. Methods: Quality and quantitative attributes of classic- and HA-NLC have been assigned based on particle size, electrokinetic potential, encapsulation efficiency, spectroscopic characteristics, and high-resolution mass spectrometry. To establish the performance profile of antioxidant activity, release of active substances, sun blocking action, and photostability, in vitro studies were conducted. Results: NLC with an average size of ~150 nm and zeta potentials < −39.5 mV showed 80% and 93.1% of encapsulation efficiency for BMDBM and EHS, and up to 83% for natural RPRF. A long-lasting release of absorbers, with a maximum cumulative release of 2.1% BMDBM and 4.6% EHS was detected. NLC-UV Abs-RPRF-HA assured 72.83% radical scavenging activity. The IC50 for HA-NLC-UV Abs-RPRF was 6.25-fold lower than NLC-UV Abs-HA, which reflects the greater free radical scavenging action. The conditioned NLC–UV Abs-RPRF-HA cream was able to provide a sun protection factor value of 52 and UVA-PF value of 81, which underlines an impressive removal of both categories of UVA and UVB radiation. A significant photoprotective upregulation, four-fold for the topical formulation with NLC-UV Abs-RPRF-HA, resulted after a simulated irradiation process. Conclusions: HA decorated-NLC-conditioned creams might provide a useful platform for developing na-tural and sophisticated dermal delivery systems, for influencing skin permeability, and for synergistically imparting antioxidant and photoprotective actions to cosmetic pro-ducts.